Bio-inspired apatite particles limit skin penetration of drugs for dermatology applications. (15th July 2020) - Choimet, Maëla; Tourrette, Audrey; Marsan, Olivier; Rassu, Giovanna; Drouet, Christophe
Abstract: Most treatments of skin pathologies involve local administration of active agents. One issue can however be the partial transcutaneous diffusion of the drug to blood circulation, leading to undesirable effects. In this work, the original use of submicron mineral particles based on bio-inspired calcium phosphate apatite was explored for the first time as drug carriers for favoring topical delivery. The permeation of a model drug across synthetic and biological membranes was investigated in both static and dynamic conditions. Our data show that adsorption of the drug on the apatite particles surface drastically limits its permeation, with lower effective diffusion coefficients (Peff ) and smaller total released amounts. The retention of the apatite colloidal particles on porcine ear skin explants surface was demonstrated by combining histological observations and Raman confocal microscopy. All results converge to show that association of the drug to apatite particles favors skin surface effects. These findings point to the relevance of mineral-based particles as drug carriers for local delivery to the skin, and open the way to novel applications of bio-inspired apatites in dermatology. Statement of Significance: Calcium phosphates (CaP) are major biomaterials in orthopedics and dentistry. Their resemblance to bone mineral allows new applications beyond bone repair, e.g. in nanomedicine. In 2018, a 14-page detailed review (M. Epple, Acta Biomaterialia 77 (2018) 1–14) provided clear facts in favor of the non-toxicity of nanosized CaP as an answer to discussions from EU and US study groups, thus clarifying the path to novel applications of nano CaP. In the present paper, bio-inspired apatite nanoparticles are used for the first time as drug carriers for dermatology for drastically limiting drug transcutaneous permeation and retaining a topical effect. We demonstrate this proof of concept via permeation cell tests, histology, Raman microscopy and photoluminescence after application on porcine ear skin. Graphical abstract: Image, graphical abstract